A chromosome-level draft genome of the grain aphid Sitobion miscanthi. Issue 8 (20th August 2019) - Jiang, Xin; Zhang, Qian; Qin, Yaoguo; Yin, Hang; Zhang, Siyu; Li, Qian; Zhang, Yong; Fan, Jia; Chen, Julian
Abstract: Background: Sitobion miscanthi is an ideal model for studying host plant specificity, parthenogenesis-based phenotypic plasticity, and interactions between insects and other species of various trophic levels, such as viruses, bacteria, plants, and natural enemies. However, the genome information for this species has not yet to be sequenced and published. Here, we analyzed the entire genome of a parthenogenetic female aphid colony using Pacific Biosciences long-read sequencing and Hi-C data to generate chromosome-length scaffolds and a highly contiguous genome assembly. Results: The final draft genome assembly from 33.88 Gb of raw data was ∼397.90 Mb in size, with a 2.05 Mb contig N50. Nine chromosomes were further assembled based on Hi-C data to a 377.19 Mb final size with a 36.26 Mb scaffold N50. The identified repeat sequences accounted for 26.41% of the genome, and 16, 006 protein-coding genes were annotated. According to the phylogenetic analysis, S. miscanthi is closely related to Acyrthosiphon pisum, with S. miscanthi diverging from their common ancestor ∼25.0–44.9 million years ago. Conclusions: We generated a high-quality draft of the S. miscanthi genome. This genome assembly should help promote research on the lifestyle and feeding specificity of aphids and their interactions with each other and species at other trophic levels. It can serve as a resource for accelerating genome-assisted improvements in insecticide-resistant management and environmentally safe aphid management.